2007
DOI: 10.1038/sj.jp.7211878
|View full text |Cite
|
Sign up to set email alerts
|

Systemic fungal infection is associated with the development of retinopathy of prematurity in very low birth weight infants: a meta-review

Abstract: Objective: To study the association between systemic fungal infection (SFI) and the development of retinopathy of prematurity (ROP) and severe ROP in very low birth weight (VLBW) infants by systematic review and meta-analysis.Study Design: A meta-review was performed using a fixed effects model. The exposure and outcomes studied were SFI and all ROP/severe ROP, respectively in VLBW infants. Results and effect sizes analyzed with Review Manager 4.2 software are expressed as relative risk (RR), odds ratio (OR), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
14
0
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(19 citation statements)
references
References 28 publications
(53 reference statements)
2
14
0
2
Order By: Relevance
“…Our finding that neonatal sepsis is a significant risk factor for ROP is also in keeping with previous studies [9,10,36,37] . In our univariable analyses, both bacterial sepsis and fungal sepsis were associated with increased risk of ROP, confirming one meta-analysis [38] and multiple observational studies [10,11,36] . As expected based on received knowledge, oxygen exposure was a strong predictor of ROP.…”
Section: Discussionsupporting
confidence: 61%
“…Our finding that neonatal sepsis is a significant risk factor for ROP is also in keeping with previous studies [9,10,36,37] . In our univariable analyses, both bacterial sepsis and fungal sepsis were associated with increased risk of ROP, confirming one meta-analysis [38] and multiple observational studies [10,11,36] . As expected based on received knowledge, oxygen exposure was a strong predictor of ROP.…”
Section: Discussionsupporting
confidence: 61%
“…[2][3][4][5] Recently, Dammann et al 6,7 have found some evidence in support of the contention that multiple "hits" of exposure to perinatal inflammation and infection might contribute to a gradual increase in the risk for ROP. Chen et al 8 suggested that neonatal sepsis, oxygen exposure, and low gestational age (GA) are not only independently associated with ROP occurrence, they interact and have a multiplicative effect on development of ROP.…”
mentioning
confidence: 96%
“…Similarly, restriction of the supplied oxygen concentration to 88-93% in the present study did not decrease the number of infants diagnosed with ROP [26]. The development of ROP has been attributed to several factors including oxygen treatment [21], sepsis [27], candidiasis [28], IVH [29], PDA, RDS, TPN [30], PBP transfusions [31], and steroid therapy [32], but despite this knowledge, no improvement to reduce the incidence of ROP has been developed recently.…”
Section: Discussionmentioning
confidence: 78%